Mechanical active compression-decompression versus standard mechanical cardiopulmonary resuscitation: A randomised haemodynamic out-of-hospital cardiac arrest study. (January 2022) - Berve, Per Olav; Hardig, Bjarne Madsen; Skålhegg, Tore; Kongsgaard, Håvard; Kramer-Johansen, Jo; Wik, Lars
Abstract: Background: Active compression-decompression cardiopulmonary resuscitation (ACD-CPR) utilises a suction cup to lift the chest-wall actively during the decompression phase (AD). We hypothesised that mechanical ACD-CPR (Intervention), with AD up to 30 mm above the sternal resting position, would generate better haemodynamic results than standard mechanical CPR (Control). Methods: This out-of-hospital adult non-traumatic cardiac arrest trial was prospective, block-randomised and non-blinded. We included intubated patients with capnography recorded during mechanical CPR. Exclusion criteria were pregnancy, prisoners, and prior chest surgery. The primary endpoint was maximum tidal carbon dioxide partial pressure (pMT CO2 ) and secondary endpoints were oxygen saturation of cerebral tissue (SctO2 ), invasive arterial blood pressures and CPR-related injuries. Intervention device lifting force performance was categorised as Complete AD (≥30 Newtons) or Incomplete AD (≤10 Newtons). Haemodynamic data, analysed as one measurement for each parameter per ventilation (Observation Unit, OU) with non-linear regression statistics are reported as mean (standard deviation). A two-sided p-value < 0.05 was considered as statistically significant. Results: Of 221 enrolled patients, 210 were deemed eligible (Control 109, Intervention 101). The Control vs. Intervention results showed no significant differences for pMT CO2 : 29(17) vs 29(18) mmHg (p = 0.86), blood pressures during compressions: 111(45) vs. 101(68) mmHg (p = 0.93) and decompressions: 21(20) vs. 18(18) mmHg (p = 0.93) or for SctO2 %: 55(36) vs. 57(9) (p = 0.42). The 48 patients who received Complete AD in > 50% of their OUs had higher SctO2 than Control patients: 58(11) vs. 55(36)% (p < 0.001). Conclusions: Mechanical ACD-CPR provided similar haemodynamic results to standard mechanical CPR. The Intervention device did not consistently provide Complete AD. Clinical trial registration: ClinicalTrials.gov identifier (NCT number): NCT02479152. The Haemodynamic Effects of Mechanical Standard and Active Chest Compression-decompression During Out-of-hospital CPR.